Influence of Australian Black Summer smoke in Antarctic aerosol collected on board during the R/V Laura Bassi first campaign in the Ross Sea - Scalabrin, Elisa; Barbaro, Elena; Pizzini, Sarah; Radaelli, Marta; Feltracco, Matteo; Ardini, Francisco; Girolametti, Federico; Piazza, Rossano; Gambaro, Andrea; Capodaglio, Gabriele (Università degli Studi di Napoli "Parthenope", 2023)
Biomass burning has been recognized as the largest source of primary fine carbonaceous particles, influencing the climate system and the Earth’s solar balance. During the 2019-2020 Australian bushfire season, and particularly from December to January, a lot of wildfires impacted the South-East of Australia, affecting local air quality. The huge amount of emitted smoke influenced stratospheric temperature over Antarctica and stratospheric aerosol optical properties (Damany-Pearce et al., 2022; Tencé et al., 2022). Long-range atmospheric transport to Antarctica and South America was also hypothesized. Levoglucosan is an anhydrosugar widely recognized as a key tracer of biomass combustion, because it can be only produced by the combustion of cellulose. Polycyclic aromatic hydrocarbons (PAHs) are organic compounds typically produced during combustion processes and are known to be present in wildfire smoke. In this work, levoglucosan and PAHs, together with other complementary sugars, were determined in aerosol samples collected during the XXXV Italian Expedition in Antarctica on board the R/V Laura Bassi from 6th January to 16th February 2020, at the end of the so-called Australian Black Summer. Total suspended particles (TSP) with a diameter >1 mm were collected on a circular quartz fiber filter (Filtros Anoia S.A. Filter-Lab, Barcelona, Spain) using a TE 5000 High-Volume Air Sampler (Tisch Environmental Inc., Cleves, OH, USA). The sampling system was connected to a wind control system, to avoid contamination from the ship. For this reason, the sampling lasted between 2 and 7 days and was carried out mainly in the coastal area of the Ross Sea. The results clearly indicate a contribution of Australian wildfires on Antarctic aerosol composition, by comparison with the detected levels of the same compounds during previous sampling campaigns in the Ross Sea area (Barbaro et al., 2016; Zangrando et al., 2016). Back trajectories indicate a local source of aerosol, confirming the hypothesis of long-term persistence of ...